Immunocytochemical study of Ki-67 as a prognostic marker in canine mammary neoplasia - Zuccari, Debora A. P. C. [UNESP]; Santana, Aureo E. [UNESP]; Cury, Patrícia M.; Cordeiro, José Antônio (Wiley, 2004)
Background: Canine mammary tumors are challenging for clinicians and pathologists because of complex histologic classification, low specificity of cytologic diagnosis, and unpredictable biological behavior. In histologic specimens, expression of tumor proliferation marker Ki-67, a nuclear nonhistone protein, has been shown to have prognostic value for canine mammary tumors and to correlate with malignancy and low survival rates. Objective: The objective of this study was to measure the proliferation index of canine mammary tumors by immunochemical detection of Ki-67 in cytologic specimens and to determine its relationship to clinical and pathologic variables and patient outcome. Methods: Spontaneous mammary tumors from 31 female dogs were surgically excised. Imprint specimens for cytologic evaluation were wet-fixed in ethanol; histologic specimens were prepared routinely. Immunostaining was performed with the PH 177 monoclonal antibody against Ki-67; proliferation index was graded from negative to +++. Dogs were followed for 18 months. Multivariate logistic regression analysis was used to determine correlations between immunocytochemical results, tumor and clinical variables, and patient outcome. Results: Ki-67 proliferation indices in cytologic specimens were significantly lower for nonmalignant tumors than for malignant tumors. High index values of Ki-67 were positively correlated with metastasis, death from neoplasia, low disease-free survival rates, and low overall survival rate. With the exception of 4 specimens for which cellularity was insufficient, positive expression of Ki-67 in cytologic specimens correlated with that of histologic specimens. Conclusions: The prognostic value of the Ki-67 index in canine mammary tumors by using wet-fixed cytology imprint specimens was similar to that observed previously for histologic specimens. Immunocytochemical detection of Ki-67 could improve the accuracy and value of cytology by providing safe and rapid information about malignancy and patient outcome. © 2004 American Society for Veterinary Clinical Pathology.
Keywords: Canine; Cytology; Dog; Immunocytochemistry; Ki-67; Mammary; Neoplasia; alcohol; Ki 67 antigen; monoclonal antibody; tumor marker; animal cell; animal experiment; animal tissue; antigen detection; benign tumor; breast tumor; cancer survival; cell proliferation; clinical feature; controlled study; correlation analysis; cytology; diagnostic accuracy; disease marker; dog; experimental neoplasm; female; histopathology; immunocytochemistry; immunohistochemistry; malignant neoplastic disease; multivariate logistic regression analysis; nonhuman; outcomes research; pathophysiology; prognosis; safety; statistical significance; tumor diagnosis; tumor growth; Animals; Antibodies, Monoclonal; Dog Diseases; Dogs; Female; Follow-Up Studies; Immunohistochemistry; Ki-67 Antigen; Mammary Glands, Animal; Mammary Neoplasms, Animal; Multivariate Analysis; Neoplasm Staging; Prognosis; Reproducibility of Results; Sensitivity and Specificity; Survival Analysis; Tumor Markers, Biological; Canis familiaris